Forensic Accounting and Investigative Audit on the Effectiveness of Implementing Audit Procedures in Fraud Disclosure - Dedy Sudarmadi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
Forensic accounting is a branch of accounting that focuses on investigating, disclosing, and preventing fraud and illegal activities in the business environment. Its main purpose is to identify, collect, analyze and present evidence that can be used in legal proceedings. Meanwhile, an investigative audit is an approach to auditing that is focused on investigating indications of fraud or non-compliance in the financial statements or business processes of an entity. The effectiveness of implementing audit procedures in disclosing fraud involves the application of a careful and careful methodology to identify signs or evidence of fraud in the financial statements and identify signs of fraud, the auditor uses knowledge about the mode of fraud and analysis of data to identify potential indications of fraud in transactions or financial reports, among others, by using forensic techniques. Auditors can use forensic data analysis techniques, digital examinations, and interviews to gather more in-depth and accurate evidence. Carry out segregation of duties. The auditor must examine the internal control system and ensure that there is adequate segregation of duties to prevent opportunities for fraud as well as test the substance of transactions to ensure that transactions reported in the financial statements actually occur and have a valid basis, in collaboration with the forensic team. In complex cases, the auditor needs to work with a forensic team that has special expertise in fraud analysis to detect fraud and the auditor prepares a report that provides a clear description of the fraud, along with recommendations for corrective measures and fraud prevention. The results of investigative audits are used to identify opportunities for improvement in the internal control system so that fraud can be minimized. Forensic accounting and investigative auditing have an important role in helping businesses detect, address and prevent fraud through a careful and evidence-based approach, effective audit procedures can reveal potential fraud and provide guidance for necessary improvements in internal controls.